GC–MS and HPLC analysis of bioactive compounds in Globe artichoke extract to enhance antioxidant and antibacterial properties in low-salt Domiati cheese - Samir Mahgoub; Salem AL-Awadi; Hassan Abdelfatah; Garsa Alshehry; Walaa E. Alhassani; Amal F. Alqurashi; Amera N. Alqahtani; Fatma I. El-Zamik (Applied Food Research)
Supplementing food with bioactive compounds offers a promising strategy for improving health. The main objectives of the study were to identify the most effective polyphenols, antioxidant and antimicrobial of the ethanolic extract of artichoke leaves (EEAL) agent against pathogens (Listeria monocytogenes, L. innocua, Staphylococcus aureus, Bacillus cereus, Salmonella enterica, Escherichia coli and Pseudomonas aeruginosa) as well as to evaluate the effects of the EEAL enriched soft, low-salt cheese (Domiati) on pathogenic bacteria, the shelf life, physicochemical properties and sensory qualities. The ethanolic extract of artichoke leaves (70 % ethanol) was analyzed using HPLC and GC–MS. The antimicrobial potential was assessed using the agar well diffusion assay and minimum inhibitory concentration (MIC) tests. The results showed that the EEAL exhibited the highest Total phenolic content (TPC) (185.27 4.30 mg GAE/g) and Total flavonoid content (TFC) (39.73 2.11 mg QUE/g), while the DPPH for ethanolic and water solvent extract (24.31 and 79.34 %), respectively. The natural extracts showed significantly (p < 0.5) antimicrobial and antioxidant effects at hydroalcoholic mix used for extraction. Significantly, leaves extract exhibited abroad-spectrum activity against the pathogens tested and showed large inhibition zone and bactericidal effects. The results indicated that supplementing soft low-salt cheese with natural byproduct leaf extracts improved its safety, as well as its physicochemical and microbiological properties, when stored at 4 °C for 40 days. Thus, this study highlights the potential of phenolic-rich artichoke leaves as ingredients for food, feed, and nutraceuticals.